2009
DOI: 10.1097/fjc.0b013e3181bad05d
|View full text |Cite
|
Sign up to set email alerts
|

Fenofibrate Enhances Neovascularization in a Murine Ischemic Hindlimb Model

Abstract: Fenofibrate have been illustrated to stimulate nitric oxide (NO) pathway, which plays pivotal roles in neovascularization. Here, we evaluated the effect of fenofibrate on neovascularization using a murine ischemic hindlimb model. C57BL/6J mice were treated with fenofibrate and/or NG-nitro-l-arginine methyl ester hydrochloride (l-NAME) for 28 days after ischemia operation. We exploited a concentration of L-NAME that did not affect blood pressure levels but suppress NO activity. Limb blood perfusion and capillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
3
11
0
Order By: Relevance
“…In agreement with our data, fenofibrate treatment leads to an increase in revascularization in ischemic hindlimbs (14). Likewise, another PPAR␣ agonist, WY-14643, promotes neovascular growth in a model of angiogenesis in the mouse cornea (5).…”
Section: E563supporting
confidence: 80%
See 3 more Smart Citations
“…In agreement with our data, fenofibrate treatment leads to an increase in revascularization in ischemic hindlimbs (14). Likewise, another PPAR␣ agonist, WY-14643, promotes neovascular growth in a model of angiogenesis in the mouse cornea (5).…”
Section: E563supporting
confidence: 80%
“…A recent analysis of the FIELD study has shown that fenofibrate suppresses the occurrence of a lower limb amputation in patients with type 2 diabetes (28). Consistent with these clinical observations, several experimental studies have indicated that, in addition to its lipid-lowering effect, fenofibrate has beneficial effects on the vascular wall, including improvement of endothelial function and revascularization (2,14,37). However, the precise mechanism of how fenofibrate regulates vascular function is incompletely understood.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…Other research has demonstrated antiangiogenic effects of fibrates leading to suppressed tumor growth [40]. In contrast, fenofibrate enhanced neovascularization in a murine hind-limb ischemia model [41] and in a murine corneal model of angiogenesis [42]. …”
Section: Pparα and Angiogenesismentioning
confidence: 99%